2015
DOI: 10.1590/0100-69912015005014
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy in uterine cervical cancer. Current state and literature review

Abstract: ABSTRACT ABSTRACT ABSTRACTCervical cancer remains the most frequent gynecological tumor in Brazil and other developing countries. Minimally invasive techniques, especially laparoscopy, have been increasingly employed in such tumors. This article aims to describe the main applications of laparoscopy in the treatment and staging of cervical cancer. In the early stages, it is possible to provide a fertilitypreserving surgery in the form of radical trachelectomy and, in a study protocol, the function-preserving su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
1
0
3
Order By: Relevance
“…Cabe destacar que, dentre os cânceres do trato genital, o câncer do colo do útero foi o mais frequente na população estudada, sendo que nos estádios avançados, a radioterapia é uma das terapêuticas de eleição (17) . Assim, justifica-se o número de atendimentos no cenário do estudo, relacionado à exclusividade do tratamento por braquiterapia no Estado de Santa Catarina até o ano 2016 ao cenário do estudo.…”
Section: Discussionunclassified
“…Cabe destacar que, dentre os cânceres do trato genital, o câncer do colo do útero foi o mais frequente na população estudada, sendo que nos estádios avançados, a radioterapia é uma das terapêuticas de eleição (17) . Assim, justifica-se o número de atendimentos no cenário do estudo, relacionado à exclusividade do tratamento por braquiterapia no Estado de Santa Catarina até o ano 2016 ao cenário do estudo.…”
Section: Discussionunclassified
“…Five studies reported, in addition to data related to voiding dysfunction, female sexual dysfunction. 9 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 Only five studies used validated questionnaires in their data collections, the rest used standardized instruments in their respective collection fields ( Charts 1 and 2 ). The studies had a variation in patient follow-up from 3 months to 9 years.…”
Section: Resultsmentioning
confidence: 99%
“…Conforme observado no quadro 1, o estudo em questão demonstrou que a histerectomia é um método de escolha quando o câncer do colo uterino se encontra avançado ou quando os outros métodos de tratamento não obtiveram o sucesso esperado. Ainda há controvérsias na literatura referente ao momento exato para a realização do procedimento, tendo em vista que alguns autores defendem a idéia de que o procedimento seja realizado nos estágios iniciais da doença (Tsunoda et al, 2015;Oliveira et al, 2021;Naumann 2020).…”
Section: Discussionunclassified